2014
DOI: 10.1177/1753495x14547428
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of skin barrier function in pregnancy and the postnatal period

Abstract: TEWL increases slightly in pregnancy and the postnatal period. The clinical significance of this is unclear and requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Research shows that the TEWL values of pregnancy have steadily increased over time, but still within normal limits, 24 consistent with our results. From this, we speculate that the decrease of skin barrier function during pregnancy may be related to the decrease of saturated fatty acid content in SSL.…”
Section: From the Results Of Ssl Analysis In Pregnancies And Controls The Decrease Of Saturated Fatty Acid Content In Pregnancy Seems To supporting
confidence: 93%
“…Research shows that the TEWL values of pregnancy have steadily increased over time, but still within normal limits, 24 consistent with our results. From this, we speculate that the decrease of skin barrier function during pregnancy may be related to the decrease of saturated fatty acid content in SSL.…”
Section: From the Results Of Ssl Analysis In Pregnancies And Controls The Decrease Of Saturated Fatty Acid Content In Pregnancy Seems To supporting
confidence: 93%
“…Trans Epidermal Water Loss (TEWL) refers to the total amount of water loss through the skin, which can be used as an index of skin barrier function for non-invasive measurement. A previous study found that TEWL increases in pregnancy and the postnatal period 6 . Lipids significantly affect the skin state through different mechanisms, such as maintaining the barrier properties of the skin and acting as signaling molecules to transmit intercellular signals 7 , 26 .…”
Section: Discussionmentioning
confidence: 90%
“…psoriasis, and atopic dermatitis [AD]), may worsen or improve during pregnancy, and pregnancy-specific skin diseases, such as intrahepatic cholestasis and pruritic urticarial papules, may occur 3 . Skin diseases during pregnancy have received extensive attention and research 4 , 5 and often occur in close association with, changes in skin condition 6 . Therefore, we speculated that the state of the skin changes and is prone to some skin diseases during pregnancy, but at the molecular level, the specific changes that take place remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation